Perfil epidemiológico de pacientes atendidos pelo serviço de atendimento móvel de urgência (SAMU) na região de São José do Rio Preto - Pezarini Junior, Clemente (2018)
A Brazilian Mobile Medical Emergency Service (SAMU) provided care for approximately 92.7 million people in 926 municipalities. Currently, it comprises 114 mobile emergency services. Objective: To investigate the epidemiological profile of patients assisted by the ambulance service in the region of São José do Rio Preto, SP. Casuistry and Methods: Epidemiological data regarding the care provided to consecutive patients by the ambulance service were evaluated in 31 municipalities in the region of São José do Rio Preto. The patients´ age and gender were analyzed, the regional coverage with the number of users per 1,000 inhabitants, number of responses per day, type of call and the demand for main medical specialties and institutions in São José do Rio Preto to treat the patients. Results: From January to September 2015, this ambulance service provided care to 93,566 patients. Monday was the day with the highest number of patients attended, and Sunday had the lowest number (ranging from 12,400 to 14,400). The number of calls by mistake was minimal (n = 1). The number of responses per 1000 inhabitants ranged from 0.42 to 39.01 in the 31 municipalities of the region. Mendonça was the municipality that had the highest number of requests for ambulances and Zacarias, the lowest. Medical Clinics (n = 5063), followed by Orthopedics (n = 1324), General Surgery (n = 974), Pediatrics (n = 774), Gynecology and Obstetrics (n = 753), Cardiology (n = 353) and Ophthalmology (n = 254) were the most requested medical specialties. In relation to the age, the highest demand of age group was 20-29 years old, followed by 30-39 years. Female patients required the services mostly on every day of the week, while requirements by the men were more common on Sundays, Mondays, Tuesdays, Thursdays and Fridays. Conclusions: The number of patients attended by SAMU ranged according to each municipality, gender and age group, but there were similar numbers of responses by day of the week. The majority of patients was in the most productive age range, that is, between 20 and 39 years old. Medical Clinics specialty presented the highest demand. Strategies to facilitate the movement of the vehicles are important regarding to response- time. The number of calls by mistake was extremely low. Hospital de Base, Santa Casa de Misericórdia and IELAR Hospital are considered of major importance to receive patients attended by the ambulance service SAMU.